Kewenangan Pemerintah Provinsi Bali dalam Pengawasan terhadap Pramuwisata yang Tidak Berlisensi - Putu Ananda Sari; Ida Ayu Putu Widiati; I Nyoman Sutama (Fakultas Hukum, Universitas Warmadewa, 2020)
Control of unlicensed tour guides is the authority of the Bali provincial government through Civil service police Unit (Satpol PP) as a form of oversight of all regional regulations, especially regional guide regulations. SatPol PP is granted the authority to supervise by the government and cooperate with court police and tourism institutions in the law enforcement system. This study discusses the authority of the Bali Provincial Government in supervising unlicensed tour guides and sanctions against unlicensed tour guides. The method used to achieve these goals is the empirical legal research method, which is to conduct field research through interviews and taking notice of the existing phenomena in society related to the problems being studied. The results of the data analysis show that the government is provided the authority by statutory regulations through Law Number 10 of 009 concerning Tourism and Regional Regulation of the Province of Bali Number 5 of 2016 concerning Tour Guides. Supervision is carried out through preventive and repressive measures and is in the law enforcement system. Sanctions are applied to tour guides who are not licensed by imposing sanctions in the form of fines through court proceedings and tour guides who commit violations will be subject to tourism violations in the form of fines. The implementation is carried out through the secrets of the tour guides when carrying out their duties in each tourism area in Bali. Guiding secrets are executed through the control function in each working area.